The Environmental Movement in Ireland - Leonard, Liam.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Collective responses to Ireland's dramatic transformation from a primarily agrarian and rural society to an industrialised economy obsessed by rapid growth and development occurred in two phases: Phase One took place between the "No Nukes" protests of the late 1970's when campaigns targeted multinational plants or infrastructural projects perceived as a pollution threat during years of economic stagnation. Phase Two occurred after economic buoyancy was achieved, as the demands of rapid growth threatened communities, the environment and Irish heritage in the face of major infrastructural projects such as roads, incinerators and gas pipelines. Starting with the Woodquay protests in Dublin, the "No Nukes" protests at Carnsore Point, the "Shell to Sea" campaign in Mayo and the campaign to save Tara from destruction, these significant ecological campaigns, based on the community's localised sense of place or rural sentiment, have formed the response to these challenges which are analysed here using social movement theories such as resource mobilisation, political opportunity, framing and event analysis.
Politics -- The Environmentalism Debate -- Irish Environmental Activism: From Woodquay to the 'Celtic Tiger' -- The Environmental Protection Agency and the Irish Green Party -- Communities -- Rural Sentiment and the Irish Environmental Movement -- Rural Sentiment as Ecological Capital -- Understanding Collective Action -- Campaigns: Phase One -- No Nukes: Carnsore Point -- The Anti-toxics Movement -- Mining: Tynagh and Donegal -- Campaigns: Phase Two -- Conservation: Mullaghmore -- Anti-incineration: Galway, Meath and Cork -- Resources: The Rossport 5 (Shell to Sea) -- Roads: Glen of the Downs, Carrickmines and Tara -- Conclusion: Mapping the Consequences of Environmental Activism.
Keywords: ENVIRONMENTAL SCIENCES; ENVIRONMENTAL LAW; ANTHROPOLOGY; POLITICAL SCIENCE; SOCIOLOGY; APPLIED PSYCHOLOGY; ENVIRONMENT; ENVIRONMENT, GENERAL; SOCIOLOGY; POLITICAL SCIENCE; ENVIRONMENTAL LAW/POLICY/ECOJUSTICE.; ANTHROPOLOGY; COMMUNITY AND ENVIRONMENTAL PSYCHOLOGY